Actividad citotóxica del aceite esencial de Plumbago scandens L. en Leishmania naiffi - Maldonado Pineda, Maritza Dayanara (2023)
Leishmaniasis is an infectious disease of man caused by flagellated protozoa of the genus Leishmania, transmitted to man by the bite of infected insects, it presents two stages; intracellular or amastigote and extracellular or promastigote. Its clinical manifestations are cutaneous (LC), mucocutaneous (CML) and visceral leishmaniasis (VL) leishmaniasis. Pentavalent antimonials such as meglumine antimonate (Glucantime®) and sodium stibogluconate (Pentostam®) are used to treat the infection. In traditional medicine, medicinal plants are used to treat this disease, without full knowledge of their benefits and mechanisms of action, one of them being Plumbago scandens L. (Plumbaguinaceae), as an alternative against leishmaniasis. The present work of curricular integration considered the cytotoxic evaluation of the essential oil of P. scandens L. obtained by steam entrainment in promastigotes of L. naiffi by the MTT colorimetric method, read at a maximum absorbance of 570 nm of wavelength that were calculated by the percent inhibition formula. The reference drug and positive control in this study was AmB. The corresponding protocols for the cytotoxic evaluation in leishmania species were drafted; the results showed that the AE inhibits the parasite by 77.99% in the concentration of 120 µg/ml. The behavior of the AmB turned out to be striking; however, it presented a parasite inhibition of less than 50%; the results were socialized to students and teachers of the Clinical Laboratory career of the National University of Loja